The value of multiple perspectives: Problem-solving and critique in the evaluation of social acceptance research—A response to M. Wolsink. (February 2019) - Gaede, James; Rowlands, Ian H.
Abstract: Established social acceptance scholar Maarten Wolsink recently published in these pages a critique of an earlier paper of ours, also published in ERSS. In this response, we will review some of Wolsink's specific methodological concerns about our original paper, conduct some preliminary analysis to test their validity, and address the issue of 'objects of acceptance' thereafter. Suffice it to say, while we find some evidence to support Wolsink's claims and personally agree (mostly) with Wolsink's broader discussion of what social acceptance is (or, rather, should be understood as) and what research on it should aim to address, we nevertheless respectfully defend the legitimacy of both our methodological design and findings within the context of the much more limited, practical aims than those we have been read to have.